Professional Learning for Patient-Centred Obstetric Services: A Qualitative Study of Service Quality and Patient Loyalty - Lutfi, Laode Muhamad Halilintar; Yunus, Asraf; Hakim, Abdul (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Patient-centered obstetric care requires healthcare personnel to understand the patient experience and utilize feedback to improve communication, privacy, coordination, and trust. This study aimed to analyze the experiences of returning patients regarding service quality and loyalty in community-based obstetric practices in Kendari, while also identifying professional learning needs. A qualitative case study design was employed, utilizing semi-structured interviews, non-participatory observation, and document review. Data were analyzed thematically using the SERVQUAL model as a sensitizing framework. Loyalty was understood through patient narratives regarding decisions to return, recommend services, and maintain relationships with providers, rather than through quantitative scores. The findings indicate that five dimensions of service quality shape the patient experience. Empathy and assurance emerged as the strongest aspects in fostering trust, repeat visits, recommendations, and patient retention. Patients valued the staff's ability to listen, explain information clearly, respect privacy, demonstrate professional confidence, and respond to needs in a coordinated manner. The study proposes the CARE-LEARN framework, which links patient experiences with team reflection, simulation, microlearning, and continuous service improvement